SISTEM INFORMASI GEOGRAFIS PEMETAAN RUMAH MAKAN (STUDI KASUS PADA : WILAYAH MEDAN KABANJAHE) - Niskarto Zendrato; Suranta Bill Fatric Ginting (UPPM, 2017)
Geographic Information System is one of the information systems discussed in computer science, which in its integration GIS embraces and represents other information systems. GIS uses computer technology to integrate, manipulate and display information or characteristics that exist in a geographic area. With the rapid technological advances currently, especially in the field of information technology, raises an idea or idea from the author to try to implement one of the GIS application system in order to provide information about locating the position of restaurant in the city of Medan. The author tries to build a system that will simplify the search position of the restaurant position based on existing data.